Dampak Implementasi Pengintegrasian Kurikulum Terhadap Mutu Pembelajaran: Analisis Kasus MTs Sains Karimiyyah Kebasen - Winasih, Tia Mugi; Fuadi, Nur (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Abstract This research aims to find out how the combination of the Al-Azhar Curriculum with the independent curriculum in an educational institution, especially the impact it has on student intelligence, of course there are several schools that use an integration basis between the two. One of these educational institutions is MTs Ilmu Al-Karimiyyah Kebasen which seeks to discover new innovations in developing new curricula. In this research, a qualitative approach is used, a descriptive type of analysis, which will provide a description of narrative data related to the process of adopting an adaptation model for the integration of the independent curriculum and the Egyptian Al-Azhar curriculum in religious learning activities at MTs Ilmu Al-Karimiyyah Kebasen. The objectives of this research are: a. To analyze how the integration and implementation of the Merdeka curriculum model and the Egyptian Al-Azhar Curriculum are carried out at MTs Ilmu Karamiyyah Kebasen. b. To analyze how to adopt and adapt the two curricula. c) to explain the impact that occurs on students both from inhibiting and supporting factors in implementing the model between the two curricula. The results of this research conclude that the integration model in PAI learning between the Merdeka and Al-Azhar Egyptian curricula takes the form of a merger of the Ministry of Education and Culture and the Ministry of Religion. As well as the supporting factors for this integration, namely the horizontal and vertical coordination of the Kamad and the teachers' council, the Kamad's innovation ideas, the committee in this case completely supports the madrasah in its policy of finding innovation in curriculum development. The inhibiting factor is limited ability to speak Arabic due to limited understanding of language skills and education. Keywords: Integration, implementation, adaptation, impact and curriculum Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana pola penggabungan Kurikulum Al-Azhar dengan kurikulum merdeka di suatu lembaga pendidikan terutama dampak yang terjadi terhadap kecerdasan siswa, tentunya ada beberapa sekolah yang menggunakan basis integasi antara keduanya. Salah satunya lembaga Pendidikan di MTs Sains Al- Karimiyyah kebasen yang mengupayakan penemuan inovasi baru di dalam pengembangan kurikulum baru yaitu desain pengintegrasian kurikulum Merdeka dengan Al-Azhar Mesir. Dalam penelitian ini menggunakan pendekatan kualitatif jenis deskriptif analisis dengan cara memberikan gambaran data-data naratif terkait proses model adopsi adaptasi integrasi kurikulum merdeka dan kurikulum Al-Azhar Mesir dalam kegiatan pembelajaran Agama di MTs Sains Al- Karimiyyah Kebasen. Tujuan penelitian ini yaitu: a. Untuk menganalisis bagaimana Integrasi dan implementasi model kurikulum Merdeka serta Kurikulum Al-Azhar Mesir di MTs Sains Karamiyyah Kebasen. b. Untuk menganalisis cara mengadopsi dan mengadaptasikan dalam kedua kurikulum tersebut. c) untuk menjelaskan dampak yang terjadi tterhadap siswa baik dari faktor penghambat serta pendukung adanya pengupayaan penerapan model antara kedua kurikulum tersebut. Hasil dari penelitian ini menyimpulkan bahwa model integrasi di pembelajaran PAI antara kurikulum Merdeka dan Al-Azhar Mesir berbentuk penggabungan dari Kemendikbud dan Kemenag. Serta faktor pendukung dari pengintegrasian itu yakni koordinasi horizontal dan Vertikal Kamad serta dewan guru, ide pemikiran inovasi kamad, komite dalam hal tersebut sepenhnya sangat mendukung madrasah dalam kebijakannya menemukan inovasi pengembangan kurikulm. Adapun faktor penghambatnnya yakni keterbatasan kemampuan dalam berbahasa Arab karena adanya keterbatasan pemahaman skil berbahasa dan pendidikan. Kata Kunci: Integrasi, implementasi, adaptasi, dampak dan kurikulum